Effect of Salinity on the Steady-State and Dynamic Rheological Behavior of Illite Clay - Zhichao Liang; Wenyuan Ren; Sha Li; Aijun Zhang; Wenjing Mi; Yuguo Wang; Bin Dang (Buildings, 2025)
The rheological behavior of clay in a water–salt environment determines the long-term deformation and structural stability of building materials and geotechnical engineering. In this study, the effects of salinity on the rheological behavior and microstructure stability of the clay mineral illite were investigated through steady-state and dynamic rheological tests. The results reveal that specimens with different salinities exhibit shear thinning behavior during the steady-state rheological test. When the shear rate is higher than 0.5 s−1, the flow curves are described well by the Herschel–Bulkley model. As the salinity increases from 0 to 1.8 mol/L, the yield stress varies from 1500 to 3500 Pa. With the increase in salinity, the consistency factor of the specimens increases, while the flow coefficient decreases. Under dynamic loading, high-salinity specimens exhibit higher modulus and yield stresses, thereby enhancing the stability of the microstructure. The viscoelastic–plastic constitutive model under dynamic loading has been established, which can effectively describe and calculate the long-term deformation of clay minerals. These research results provide reference and guidance for understanding the rheological behavior of clay.